PENGARUH PELATIHAN DAN PEMBINAAN TERHADAP PENGEMBANGAN USAHA KECIL - Irawati, Rina (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
Small businesses have a central role in the Indonesian economy. Small businesses have supporting economic sector development. The large number is unfortunately not accompanied by the maximum quality of education from SMEs. To develop a small business, of course, training and coaching are required. The purpose of this study was to examine the effect of training and coaching simultaneously and partially on the development of small business. The sample of this research is 76 small medium entrepreneurs in Lowokwaru Malang, with purposive sampling technique. The result of multiple regression test proves that there is influence simultaneously and partially between training and coachingto small business development. It means research hypothesis was accepted. The dominant variable that influences is coaching (X2) with the largest beta value of 0.675.